The elite illusion: Achievement effects at Boston and New York exam schools - Atila Abdulkadiroğlu; Joshua David Angrist; Parag A. Pathak (Institute for the Study of Labor (IZA), 2012)
Parents gauge school quality in part by the level of student achievement and a school's racial mix. The importance of school characteristics in the housing market can be seen in the jump in house prices at school district boundaries where peer characteristics change. The question of whether schools with more attractive peers are really better in a value-added sense remains open, however. This paper uses a fuzzy regression-discontinuity design to evaluate the causal effects of peer characteristics. Our design exploits admissions cutoffs for Boston and New York City's heavily over-subscribed exam schools. Successful applicants near admissions cutoffs for the least selective of these schools move from schools with scores near the bottom of the state SAT score distribution to a school with scores near the median. Successful applicants near admissions cutoffs for the most selective of these schools move from above-average schools to schools with students drawn from the extreme upper tail. Exam school students can also expect to study with fewer nonwhite classmates than unsuccessful applicants. Our estimates suggest that the marked changes in peer characteristics at exam school admissions cutoffs have little causal effect on test scores or college quality.
Keywords: I21; I28; C21; 330; human capital; peer effects; school quality